'Best practice' in developing and evaluating palliative and end-of-life care services: A meta-synthesis of research methods for the MORECare project. (December 2013) - Evans, Catherine J; Harding, Richard; Higginson, Irene J; ,
Background: Improved and cost-effective palliative and end-of-life care is an international policy imperative. Developments are impeded by a weak and often inconsistent evidence base. Aim: To examine the main methodological challenges and limitations to developing and evaluating palliative and end-of-life care services and requirements to further this field of research. Design: A meta-synthesis to systematically appraise the evidence from systematic reviews on the research methods used in studies evaluating the effectiveness of palliative care services for patients with advanced illness and/or carers meeting inclusion and quality criteria. We extracted data from the reviews on the methodological issues reported on the included studies into Excel spreadsheets and generated textual descriptions coded and analysed in NVivo. Data sources: Six electronic databases, reference chaining and expert advice. Results: In total, 27 systematic reviews were included on the effectiveness of palliative care services for patients with cancer ( n = 6), advanced illness ( n = 10) or mixed populations ( n = 11) across care settings. Main methodological challenges were implementation as a continuum, active precise recruitment, addressing randomisation and economic evaluation beyond cost savings. Conclusions: The complexity of delivering and evaluating palliative and end-of-life care services requires the accumulation of knowledge from multiple sources to understand the active components of an intervention to deliver patient benefit and examine the evaluation methods to detect change and reveal processes prior to a definitive trial. The implementation of evidence into practice should form a continuum throughout the evaluation stages to reveal understanding on the process of intervention delivery, the context and the intended outcome(s).